ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI PEMANFAATAN KELAS IBU HAMIL DI UPTD PUSKESMAS NAMORAMBE KECAMATAN NAMORAMBE TAHUN 2025 - Sembiring, Sella Elita (Deli Medical and Health Science Journal, 2025)
Improving maternal health remains a priority in public health, particularly in efforts to reduce deaths among mothers and newborns. One initiative aimed at addressing this is the Pregnancy Class program, which provides education on antenatal care, childbirth readiness, and infant care. However, Indonesia still faces significant barriers in lowering maternal mortality rates to meet the 2030 Sustainable Development Goals, which target fewer than 70 deaths per 100,000 live births. This study investigates what factors affect attendance in Pregnancy Classes at Namorambe UPTD Health Center in 2025. A cross-sectional quantitative method was used, involving 66 pregnant women selected from a total of 79 through proportional stratified random sampling. Data collection was conducted using structured questionnaires, and analysis was carried out through univariate, bivariate, and multivariate techniques, including chi-square tests. Results showed meaningful relationships between class participation and variables such as age (p<0.001; OR=9.4), employment (p<0.006; OR=5.5), knowledge (p<0.004; OR=7.1), infrastructure (p<0.002; OR=8.5), partner support (p<0.005; OR=8), and healthcare worker involvement (p<0.009; OR=6.5). The study concludes that these elements significantly influence involvement in the Pregnancy Class program, with knowledge emerging as the strongest contributing factor.